Automatic imaging of Drosophila embryos with light sheet fluorescence microscopy on chip. Issue 3 (16th December 2020) - Memeo, Roberto; Paiè, Petra; Sala, Federico; Castriotta, Michele; Guercio, Chiara; Vaccari, Thomas; Osellame, Roberto; Bassi, Andrea; Bragheri, Francesca
Abstract: We present a microscope on chip for automated imaging of Drosophila embryos by light sheet fluorescence microscopy. This integrated device, constituted by both optical and microfluidic components, allows the automatic acquisition of a 3D stack of images for specimens diluted in a liquid suspension. The device has been fully optimized to address the challenges related to the specimens under investigation. Indeed, the thickness and the high ellipticity of Drosophila embryos can degrade the image quality. In this regard, optical and fluidic optimization has been carried out to implement dual‐sided illumination and automatic sample orientation. In addition, we highlight the dual color investigation capabilities of this device, by processing two sample populations encoding different fluorescent proteins. This work was made possible by the versatility of the used fabrication technique, femtosecond laser micromachining, which allows straightforward fabrication of both optical and fluidic components in glass substrates. Abstract : Here we present a fully integrated device for automatic imaging of Drosophila embryos, by light sheet fluorescence microscopy. The chip, constituted by both fluidic and optical components, is fully optimized to automatically process Drosophila embryos.